Lysophosphatidic acid acyltransferases: a link with intracellular protein trafficking in Arabidopsis root cells?. (19th November 2021) - Wattelet-Boyer, Valérie; Le Guédard, Marina; Dittrich-Domergue, Franziska; Maneta-Peyret, Lilly; Kriechbaumer, Verena; Boutté, Yohann; Bessoule, Jean-Jacques; Moreau, Patrick
Abstract: Phosphatidic acid (PA) and lysophosphatidic acid acyltransferases (LPAATs) might be critical for the secretory pathway. Four extra-plastidial LPAATs (LPAAT2, 3, 4, and 5) were identified in Arabidopsis thaliana. These AtLPAATs display a specific enzymatic activity converting lysophosphatidic acid to PA and are located in the endomembrane system. We investigate a putative role for AtLPAATs 3, 4, and 5 in the secretory pathway of root cells through genetical (knockout mutants), biochemical (activity inhibitor, lipid analyses), and imaging (live and immuno-confocal microscopy) approaches. Treating a lpaat4;lpaat5 double mutant with the LPAAT inhibitor CI976 produced a significant decrease in primary root growth. The trafficking of the auxin transporter PIN2 was disturbed in this lpaat4;lpaat5 double mutant treated with CI976, whereas trafficking of H + -ATPases was unaffected. The lpaat4;lpaat5 double mutant is sensitive to salt stress, and the trafficking of the aquaporin PIP2;7 to the plasma membrane in the lpaat4;lpaat5 double mutant treated with CI976 was reduced. We measured the amounts of neo-synthesized PA in roots, and found a decrease in PA only in the lpaat4;lpaat5 double mutant treated with CI976, suggesting that the protein trafficking impairment was due to a critical PA concentration threshold. Abstract : Phosphatidic acid produced by lysophosphatidic acid acyltransferases has an impact on the efficiency of the intracellular trafficking of some proteins in Arabidopsis thaliana root cells.